Occupants’ Interaction With an Occupant Voting System for Thermal and Indoor Air Quality Feedback – Case Studies in Office Spaces - Sheikh Khan, Donya; Kolarik, Jakub; Weitzmann, Peter (Frontiers in Built Environment, 2021)
Occupants can provide valuable feedback on the indoor environmental quality of buildings. Research on occupant voting systems (OVS) has demonstrated that apps or electronic devices can act as viable tools for collecting long-term feedback from occupants. However, previous research has only to a limited extent explored occupants’ interaction with OVS and the impact it might have on the reliability of the collected feedback. The present paper presents three case studies on applying a tangible OVS, denoted TiAQ, to collect feedback on thermal and indoor air quality (IAQ) in office spaces. The main objective of the present study was first to explore occupants’ interaction with TiAQ and their motivation. Second, identifying whether feedback collected with TiAQ could represent occupants’ comfort and discomfort with the thermal environment and IAQ. Thirdly, identifying challenges related to occupants’ interaction with TiAQ that might affect the representativeness of collected feedback. The present study was conducted at three office buildings in up to seven months and demonstrated that TiAQ was suitable for collecting long-term feedback on occupants’ comfort and discomfort with the thermal environment. On average, one vote was cast per day per occupant. Additionally, in one of the office buildings, 60% of occupants reported to have interacted with TiAQ daily or weekly when e.g. passing the device going to/from the office spaces. Occupants’ expectations of TiAQ and getting “feedback on feedback” need to be further addressed to identify ways to sustain occupants’ long-term use of the device and reduce “ill-willed” interactions.